Challenges and Opportunities of Postmodernism in Christian Counseling: A Conceptual Review of Theological and Epistemological Integration - Lucyana Senjaya; Junifrius Gultom (Universitas Negeri Padang, 2026)
Combining postmodern epistemology with Christian counseling prompts core questions about truth, narrative identity, and relational healing. Objective: This study explores the tensions and opportunities that emerge when postmodern therapeutic methods intersect with Christian theological principles. A systematic review of the literature was conducted across five databases: ERIC, Scopus, Garuda Garba, Google Scholar, and Dimensions. The search was limited to peer-reviewed journal articles published in English or Indonesian from 2007 to 2026. Out of 4,505 records initially retrieved, 377 were downloaded for screening. After applying specific inclusion and exclusion criteria—such as focusing on peer-reviewed articles (IC1) and the date range (IC2)—15 articles were included in the final review. Foundational works prior to 2007 (e.g., Blanton, 2004, 2005; Watson, 2004) are cited only for background and are not included in the analysed set. The literature highlights three main themes: (1) the conditional potential for integrating narrative and relational postmodern techniques within Christian counseling; (2) ongoing philosophical and theological tensions—particularly about epistemological relativism and scepticism toward grand narratives—that scholars discuss from differing viewpoints without reaching consensus; and (3) notable gaps in counselor education and methodological implementation. The integration of postmodern insights into Christian counseling is still debated and depends heavily on context. The link between postmodern epistemology and Christian theology calls for a critical, selective, and theologically responsible engagement rather than unrestricted adoption.